Konflik Etis dalam Hubungan Guru dan Siswa di SMK Swasta HKBP Sarulla - Rencan Charisma Marbun; Melise Diana Nahampun; Rumentha Afrianti Simanungkalit (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This research discusses ethical conflicts arising in the teacher-student relationship at SMK Swasta HKBP Sarulla. Against the backdrop of Biblical values and the unique mission of Christian education, teacher-student relationships often involve complex moral and spiritual dimensions.​​ The study aims to identify the types of ethical conflicts that occur, analyze their causal factors, and understand the resolution processes as well as their impacts on individuals and the school environment. Employing a qualitative approach, this case study involves in-depth interviews with teachers, students, and the principal, along with analysis of internal school documents.​ Initial findings indicate that ethical conflicts often stem from differing interpretations of Christian values, role expectations, and ineffective communication. The implications of this study highlight the importance of comprehensive ethics training, the development of clear ethical codes, and conflict resolution mechanisms sensitive to the Christian school contextKeywords: Ethical Conflict, Teacher-Student Relationship, Christian School, Educational Ethics, Case Study. Keywords: Ethical Conflict, Teacher-Student Relationship, Christian School, Educational Ethics, Case Study.   Abstrak Penelitian ini membahas tentang konflik etis yang muncul dalam hubungan guru dan siswa di SMK Swasta HKBP Sarulla. Dengan latar belakang nilai-nilai Alkitabiah dan misi pendidikan Kristen yang berbasis Alkitabiah, hubungan guru-siswa seringkali melibatkan dimensi moral dan spiritual yang kompleks. Penelitian ini bertujuan untuk mengidentifikasi jenis konflik etis yang terjadi,  menganalisis faktor-faktor penyebabnya, dan memahami proses resolusi serta dampaknya terhadap individu dan lingkungan sekolah. Menggunakan pendekatan kualitatif, penelitian studi kasus ini melibatkan wawancara mendalam dengan guru, siswa, dan kepala sekolah, serta analisis dokumen internal sekolah. Temuan awal menunjukkan bahwa konflik etis seringkali berakar pada interpretasi yang berbeda terhadap nilai-nilai Kristen, ekspektasi peran, dan komunikasi yang tidak efektif. Implikasi studi ini menyoroti pentingnya pelatihan etika yang komprehensif berbasis kasih keadilan, integritas, pengembangan kode etik yang jelas, dan mekanisme resolusi konflik yang peka terhadap konteks sekolah Kristen. Kata Kunci: Konflik Etis, Hubungan Guru-Siswa, Sekolah Kristen, Etika Pendidikan, Studi Kasus.